ANALYSIS OF FOREIGN DIRECT INVESTMENT (FDI) IMPACT ON POVERTY IN INDONESIA 2010 UNTIL 2014 - Fathur Rochman; Widya Sylviana (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Foreign Direct Investment (FDI) is one of the important factors that can improve a country's economy, both in increasing economic growth, opening new jobs and reducing poverty. This study aims to analyze the impact of FDI on provincial poverty levels in Indonesia in 2010 to 2014. The study used quantitative research methods with a regression equation model used in research that is panel data regression method. The panel regression model used is the Fixed Effect Model (FEM) with the Generalized Least Square (GLS) healing method. The method used in this study is the econometric approach. The study result indicates economic growth, FDI, number of labor force, and government expenditure negatively and significantly affects poverty levels in Indonesia. The impact of having a Foreign Direct Investment (FDI) can reduce the provincial poverty rate in Indonesia from 2010 to 2014.